Written expression for professional communication in the process of English language training for journalism students ni - Caballero Arias, Rolando; Roman Betancourt, Midalys Roman; Martínez Adams, Yaneisy (Transformación, 2025)
Objetive
Keywords: Higher education; Professional education; Languages development